Rupture infected pseudoaneurysm on brachiocephalic AV-fistula: emergency and definitive management - Reza Eka Putra; Prasetyo Edi (Journal of Indonesia Vascular Access, 2022)
Background: Vascular access bleeding is a rare event that can be fatal in hemodialysis patients. It requires emergency and surgical management to reduce the risk of ischemic events in the patient’s forearm and reduce mortality risk. Objective: To describe the clinical presentation, emergency and surgical intervention, and outcome of rupture-infected anastomotic pseudo aneurysm of the brachiocephalic arteriovenous fistula that underwent a definitive surgical procedure. Case Description: A 55-year-old man presented with bleeding on the AV-fistula surgery site, accompanied with pain and swelling on his forearm that occurred 3 hours before admission to the hospital. The Patient had a history of brachiocephalic AV-fistula surgery 3 weeks earlier. On physical examination, It was found that the surgical site wound looked wet and swollen, with lots of necrotic tissue and pus and lost stitches. In Emergency Departments, the patient was administered intravenous normal saline fluids, bleeding inhibitors and pressure bandages to reduce ongoing bleeding. Then the patient had planned for immediate vascular reconstruction surgery. The brachial artery is repaired using great saphenous vein patch plasty. Results: The patient’s postoperative 30-days follow-up went well, and there was no sign of complication, such as pain, infection, paresthesia, bleeding at the surgical site or ischemia in the distal forearm. Conclusion: Vascular access bleeding can be fatal to hemodialysis patients. Optimal treatment for the patient's life and hemodialysis access is a top priority. A good assessment of the condition of AVF and the choice of subsequent therapy greatly affect the patient's prognosis.